The growth rate of Cladonia rangiferina and C. mitis in relation to forest characteristics in northeastern Finland - Helle, Timo; Aspi, J.; Tarvainen, L. (Rangifer, 1983)
The growth rate of Cladonia rangiferina and C. mitis was studied in Kuusamo, northeastern Finland, where they share more than 90 percent of the total lichen biomass. The material was collected from 5 pine forests of different ages in Calluna-Cladina heaths. The length growth rate of C. rangiferina varied by site from 3.9 to 4.3 mmyr -' and that of C. mitis from 3.0 to 3.5 mmyr-1 C. rangiferina achieved the fastest growth in a younger (60 years) shadowy forest; growth was slowest in a clear-felled area and in an old (180 years), already thinned forest. C. mitis grew fastest in a site with young (10 years old) pine plants and slowest in a younger shadowy site. The results do not support suggestions that clear-felling itself might negatively influence the growth of lichens. However, it is important also from the point of view of range management to create a new forest as soon as possible, since both species studied here grew faster in young forests than in clear-felled areas. Harmaaporonjakalan ja mietoporonjakalan kasvunopeus eri-ikaisissa metsissa. Abstract in Finnish / Yhteenveto: Harmaaporonjakalan (Cladonia rangiferina) ja mietoporonjakalan (Cladonia mitis) kasvunopeutta tutkittiin Kuusamossa. Aineisto kerattiin 5 puustoltaan eri-ikaiselti jakalakankaalta. Harmaaporonjakala kasvoi pituutta keskimaarin 3.9 - 4.3 mm/v ja mietoporonjakala 3.0 - 3.5 mm/v kasvupaikasta riippuen. Harmaaporonjakalan kasvu oli nopeinta nuorehkossa (60 v) tiheassa metsassa, hitainta paljaaksihakkuulla ja vanhassa (180 v), jo harventuneessa metsassa. Mietoporonjakala kasvoi nopeimmin 90 cm:n taimikossa ja hitaimmin varjoisimmalla kasvupaikalla. Tulosten perusteella on vaikea yhtya kasitykseen, etta paljaaksihakkuu sinansa vahentaa poronjakalien kasvunopeutta. Myos poronhoidon kannalta on kuitenkin tarkeaa, etta uusi metsa saadaan aikaan mahdollisimman nopeasti, silla molemmat lajit kasvavat nopeimmin eri-ikaisissa nuorissa metsissa.